Obstructive Sleep Apnea in Children: A Survey of the Curriculum and Screening Processes of Pediatric Residency Programs in the United States of America. - Geach, Belen. (2017)
Abstract: Introduction and Purpose: Sleep Disordered Breathing (SDB) is a potentially life-threatening condition, which encompasses a wide variety of upper airway obstructions during sleep, from primary snoring to obstructive sleep apnea (OSA). OSA is characterized by recurrent episodes of cessation of breathing followed by arousals from sleep due to complete or partial obstruction of the upper airways. It is estimated that 2% of children could be suffering from SDB; of those, 1 to 10% may have OSA. The purpose of this study was to identify pediatric dentistry residency programs that teach and screen for OSA in their programs and clinics. In addition, factors that are associated with the screening and teaching of OSA were evaluated. Materials and Methods: A survey questionnaire was U.S. Postal Service mailed and emailed to all pediatric residency programs in the United States that were affiliated with the American Academy of Pediatric Dentistry (n = 77). The questionnaire included an introductory letter and cover letter describing the purpose of the study and assurance of confidentiality. All surveys were coded to allow for identification for follow-up letters. A time period of 4 weeks was allotted for the all replies after which a reminder letter/email and copy of the questionnaire was sent a second and third time. Results: A response rate of 79% was achieved. 78% of programs teach about OSA in their formal program. However, only 41% of programs regularly screen for OSA as a routine part of the clinical exam. No significant association between program types, number of residents, number of years in dental practice of program director and teaching about OSA was found. However, there was a statistically significant positive association between programs that teach their residents about OSA and those who screen for it clinically. Eighty-two percent of respondents thought it was very/extremely important to screen for OSA, while 18% thought it was not necessary or important to screen for OSA (n=57) Conclusion: The results suggest that program directors consider this subject important enough to include in the curriculum and believe pediatric dentists can play an important role in the screening of OSA. Early recognition of this condition through screening is of utmost importance.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Other.; Advisor: Steven Scrivani.; Committee: Ron Kulich, Noshir Mehta, and Mathew Finkelman.; Keyword: Educational evaluation.